Telaah Politik Hukum Pembentukan Badan Otorita Ibu Kota Negara dalam Sistem Ketatanegaraan Indonesia - Wahyu Laksana Mahdi (CV Rewang Rencang, 2022)
After the enactment of Law Number 3 of 2022 concerning the State Capital, it has implications for the regional government system. This is a logical consequence of the a quo arrangement which designs of the Archipelago Capital Authority with a special nature and all the powers attached to the agency. The new regional government system certainly reaps pros and cons because it is considered unconstitutional and the concept of regional government is ambiguous. However, at the legal political level, the actual establishment of the Archipelago Capital Authority Agency is a manifestation of Article 18B paragraph (1) of the 1945 Constitution of the Republic of Indonesia which expressly states that the state recognizes and respects regional government units which are special and exclusive.